Analysis of dam deformation measurements with the robust and non-robust methods - Tasci, Levent (Academic Journals, 2010)
Rapid developments in engineering structures, the growing interest in studying the earth crust movements, the analysis of deformation measurements, measurement methods and precision have revealed new demands. The purpose of this study is to determine the deformations that take place on dam crest due to different water level, load and dam's body weight. Altinkaya Dam, which is a rock fill dam, was selected as application area and a deformation network consisting of 6 references and 11 object points were constructed. In this study, deformation measurements were performed between 2000 and 2002. Measurements were made every June and September, in that the water level was minimum and maximum, respectively. Hence, measurements were made in 4 periods. All measurements were performed using static GPS measurement method. In this study, Iterative weighted transformation (IWST), Least Absolute Sum (LAS), Congruency test analysis method and Fredericton were used for performing two dimensional deformation analyses.
Keywords: GPS; dam; deformation; analysis; congruency test; IWST; LAS; Fredericton